2021
DOI: 10.3389/fcell.2021.774845
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin E/CDK2: DNA Replication, Replication Stress and Genomic Instability

Abstract: DNA replication must be precisely controlled in order to maintain genome stability. Transition through cell cycle phases is regulated by a family of Cyclin-Dependent Kinases (CDKs) in association with respective cyclin regulatory subunits. In normal cell cycles, E-type cyclins (Cyclin E1 and Cyclin E2, CCNE1 and CCNE2 genes) associate with CDK2 to promote G1/S transition. Cyclin E/CDK2 complex mostly controls cell cycle progression and DNA replication through phosphorylation of specific substrates. Oncogenic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(54 citation statements)
references
References 122 publications
(167 reference statements)
1
53
0
Order By: Relevance
“…7A). As it has been demonstrated that CDK2 activation requires the formation of the cyclin E/CDK2 complex (46), we speculated that the starvationinduced cyclin E down-regulation may decrease the formation of the cyclin E/CDK2 complex, leading to the inhibition of CDK2 activity. Consistent with this hypothesis, we found that the CDK2 inhibitor roscovitine notably reduced the levels of p-SIRT2 S331 , Ac-ATG4B K39 , SQSTM1, and Ac--tubulin K40 but elevated the protein level of LC3-II (Fig.…”
Section: Starvation Activates Sirt2 By Suppressing Cyclin E/cdk2mentioning
confidence: 98%
“…7A). As it has been demonstrated that CDK2 activation requires the formation of the cyclin E/CDK2 complex (46), we speculated that the starvationinduced cyclin E down-regulation may decrease the formation of the cyclin E/CDK2 complex, leading to the inhibition of CDK2 activity. Consistent with this hypothesis, we found that the CDK2 inhibitor roscovitine notably reduced the levels of p-SIRT2 S331 , Ac-ATG4B K39 , SQSTM1, and Ac--tubulin K40 but elevated the protein level of LC3-II (Fig.…”
Section: Starvation Activates Sirt2 By Suppressing Cyclin E/cdk2mentioning
confidence: 98%
“…As a substrate of FBXW7, cyclin E, a nuclear protein that interacts with and activates cyclin-dependent kinase 2 (CDK2) to phosphorylate proteins, facilitates G 1 /S phase transition and is degraded at the boundary of the S/G 2 phase, whereas the overexpression of cyclin E has been detected in human cancer cells associated with cell cycle deregulation and chromosome instability (CIN) ( 161 , 162 ). FBXW7 mutations lead to the aberrant accumulation of its substrate cyclin E in CRC samples, conferring abnormality of chromosome congression during metaphase as well as ensuing chromosome transmission, implicating the role of FBXW7/cyclin E axis in regulating CIN ( 163 ).…”
Section: Fbxw7 and The Hallmarks Of Cancermentioning
confidence: 99%
“…This protein complex regulates cell-cycle progression and DNA replication through the phosphorylation of specific substrates. In oncogenic conditions, the Cyclin E/CDK2 complex affects normal DNA replication, causing DNA replication stress, leading to cellular instability—a precursor of cancer development [ 55 ].…”
Section: Resultsmentioning
confidence: 99%